PENAKSIRAN KESENJANGAN OUTPUT INDONESIA: APLIKASI METODE KALMAN FILTER DAN HODRICK-PRESCOTT FILTER - Priyono, Teguh Hadi (Journal of Indonesian Applied Economics, 2008)
This  research will measure  the potential output  in  Indonesia using Kalman-filterand Hodrick-Prescott Filter. The model will  observe  the variations of output  gapand inflation in Indonesia. The model of Kalman Filter shows a long-term trend ofoutput nearly to actual output than the other model, however it shows a slow responsethan Hodrick-Prescott Filter.Keywords: Output Gap, Inflation, Kalman filter and Hodrick – Prescote Filter.